Primary ciliary dyskinesia - GÖKDEMİR, YASEMİN (Springer, London/Berlin, 2023)
Primary ciliary dyskinesia (PCD) is a rare disease characterized by abnormal ciliary function due to defects in the structure and/or function of motile cilia. As the motile cilia are found on the epithelial surface of the upper and lower respiratory tract and middle ear and as they have a critical role in the local defense of the airways, dysfunction of motile cilia leads to impaired mucociliary clearance resulting in recurrent and chronic infections of the upper and lower airways [1].
Keywords: Sağlık Bilimleri; Health Sciences; Klinik Tıp (MED); Clinical Medicine (MED)